Long-term follow-up of Japanese encephalitis chimeric virus vaccine: Immune responses in children - Kulkanya Chokephaibulkit (2018)
© 2016 Elsevier Ltd Background A single dose of live attenuated Japanese encephalitis chimeric virus vaccine (JE-CV) was shown to be immunogenic and well tolerated when given either as a booster to formalin-inactivated Japanese encephalitis (JE)-vaccine (mouse brain-derived vaccine [MBDV])-primed 2–5-year-olds, or as a primary vaccination to JE-vaccine-naïve 12–24-month-old toddlers in Thailand. A 5-year follow-up assessment of immune response persistence over time was conducted. Methods Four additional visits (at 2, 3, 4, and 5 years) for immunologic assessments were added to the original 12-month open-label crossover study, in which 100 healthy children aged 2–5 years with a history of two-dose primary vaccination with MBDV (according to the Thai Expanded Program for Immunization schedule), and 200 healthy JE-vaccine-naïve 12–24-month-old toddlers, were randomized 1:1 to receive JE-CV, containing ⩾4 log10plaque forming units, 1 month before or after hepatitis A control vaccine. Results In MBDV-primed 2–5-year-olds (n = 78), the immune response to the JE-CV vaccine persisted up to at least 5 years after vaccination with a single dose of JE-CV, with all (n = 78) children seroprotected at the year 5 visit (geometric mean titers [GMT]: 252 1/dil). There was no decrease of seroprotection rate over time (100% at 6 months post-vaccination and 96.8% (90.3–98.9) at 5 years post-vaccination). In JE-vaccine-naïve toddlers, a protective immune response persisted up to at least 5 years in 58.8% (50.9–66.4) after a single-dose administration of JE-CV (GMT 26.7 1/dil; sensitivity analysis). Conclusions A single-dose of JE-CV as a booster following MBDV administration provided long-lasting immunity. In JE-vaccine-naïve toddlers, despite relatively high seroprotection rates persisting over time, a subsequent booster dose is recommended following a JE-CV primary vaccination for long-term protection. This study was registered on www.clinicaltrials.gov (NCT00621764).